The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ijerph13101025
|View full text |Cite
|
Sign up to set email alerts
|

Two Mechanisms: The Role of Social Capital and Industrial Pollution Exposure in Explaining Racial Disparities in Self-Rated Health

Abstract: This study provides an empirical test of two mechanisms (social capital and exposure to air pollution) that are theorized to mediate the effect of neighborhood on health and contribute to racial disparities in health outcomes. To this end, we utilize the Social Capital Benchmark Study, a national survey of individuals nested within communities in the United States, to estimate how multiple dimensions of social capital and exposure to air pollution, explain racial disparities in self-rated health. Our main find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…Although this study contributes to previous work by bridging the fields of social epidemiology and environmental inequality and by formally testing established theoretical models, the veracity of our results is contingent on replication with longitudinal data and more comprehensive assessments of socioeconomic status. Additional research is also needed to explore socioeconomic variations in toxin exposure and physical health in different national contexts and at different levels of analysis (Ard 2015(Ard , 2016Ard et al 2016). Research along these lines would advance our collective understanding of the environmental processes linking socioeconomic status and health.…”
Section: Resultsmentioning
confidence: 99%
“…Although this study contributes to previous work by bridging the fields of social epidemiology and environmental inequality and by formally testing established theoretical models, the veracity of our results is contingent on replication with longitudinal data and more comprehensive assessments of socioeconomic status. Additional research is also needed to explore socioeconomic variations in toxin exposure and physical health in different national contexts and at different levels of analysis (Ard 2015(Ard , 2016Ard et al 2016). Research along these lines would advance our collective understanding of the environmental processes linking socioeconomic status and health.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this materialist foundation, less emphasis in EJ research has been placed on people’s subjectivities. Several articles in this Special Issue advance EJ research by examining and clarifying stakeholder subjectivities regarding EJ issues [9,11,18,19], which extends the research framework beyond the documentation of unjust conditions and processes. In Hornik et al’s [9] study, which clarifies community group perceptions of EJ in the context of water sustainability initiatives in Milwaukee, WI, USA, stakeholders shared similar perspectives on environmental injustice as an everyday experience.…”
mentioning
confidence: 99%
“…Findings highlight the importance of media in shaping perceptions of environmental injustice, and reveal how public perceptions of injustice may be cultivated to impede societal transitions toward renewable energy sources. Ard et al [19] use multilevel models in a US national study of the roles of neighborhood social capital and exposure to industrial air pollution in explaining the racial gap in self-rated health between black, Hispanic, and white individuals. They found that individuals’ feelings of trust in neighbors of different social standing and perceptions of political empowerment largely accounted for lower self-rated health among African Americans (and partially accounted for it among Hispanics) relative to whites, while exposure to industrial air pollution was statistically irrelevant.…”
mentioning
confidence: 99%
“…Basic information about these studies are provided in Table 1. Most studies (four) were from the UK (21,23,25,28), followed by the USA (17,24,29). Two studies were from Australia (26,27), two from Belgium (20,22) and two from the Netherlands (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…(23), respondents rated their neighborhood on a scale from dangerous to safe (26), no information about measurement (30), two questions about neighborhood as a safe place to walk around at night and if people feel safe in their homes (27) General social trust [(26), (19)*] Question: if "most people can be trusted or that you can't be too careful in dealing with people?" (19), trust of people in Australia, government, and big business (26) Neighborhood trust [(17)*, (24)*, (27)] Index about generalized trust through different entities in the neighborhood (17,27), question: how much "people in the neighborhood can be trusted" (24) Group involvement [(17)*, (26), (27), (20), (22)*, (19),…”
Section: Resultsmentioning
confidence: 99%